Miranda Lida y Mariano Fabris (Coords.) La revista Criterio en el siglo XX argentino. Religión, cultura y política. Rosario: : Prohistoria, 2019, 215 pp - Camaño Semprini, Rebeca (2019)
As a journalistic enterprise as well as a cultural project, as Lida and Mauro point out, Criterio admits multiple questions and analytical approaches. Aware of the almost impossibility of encompassing all the potential dimensions of analysis opened by this Catholic journal in historical, theological, cultural, political, or intellectual terms, the authors undertake the study of a publication whose complex trajectory makes it difficult to pigeonhole.